Cultural Bridging and Employment Counselling with Clients from Different Cultural Backgrounds - Amundson, Norm; Westwood, Marvin; Prefontaine, Rose (Canadian Journal of Counselling and Psychotherapy, 2007)
Some practical strategies for building relationships and working with clients from different cultural backgrounds are outlined in this paper. Counsellors are encouraged to build bridges with clients by exploring areas of common ground. The bridge-building process often requires an understanding of the client's world in terms of family and friends. Other intervention strategies are described which include working with transferable skills and attitudes along with an intensive form of behaviour rehearsal. The paper concludes with a brief discussion of some training issues.